2022
DOI: 10.15252/embr.202154405
|View full text |Cite
|
Sign up to set email alerts
|

Isotope‐labeled amyloid‐β does not transmit to the brain in a prion‐like manner after peripheral administration

Abstract: Findings of early cerebral amyloid-b deposition in mice after peripheral injection of amyloid-b-containing brain extracts, and in humans following cadaveric human growth hormone treatment raised concerns that amyloid-b aggregates and possibly Alzheimer's disease may be transmissible between individuals. Yet, proof that Ab actually reaches the brain from the peripheral injection site is lacking. Here, we use a proteomic approach combining stable isotope labeling of mammals and targeted mass spectrometry. Specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Formalin-fixed hemispheres were embedded in paraffin and cut into 4-μm-thick coronal sections using a rotation microtome (HM355S, Leica Biosystems GmbH, Nußloch, Germany) as described previously [ 75 , 76 , 77 , 204 , 205 , 206 , 207 , 208 , 209 , 210 ]. Sections (bregma +0.8 mm and −1.8 mm) were stained for microglia (IBA1, 1:1000, FUJIFILM Wako Chemicals Europe GmbH, 019–19741), astrocytes (GFAP, 1:500, Agilent, Santa Clara, CA, USA, Z033401-2) using a BOND-III ® automated immunostaining system (Leica Biosystems GmbH, Nußloch, Germany) with a hematoxylin counterstain (provided with the staining kit, Bond Polymer Refine Detection, DS9800).…”
Section: Methodsmentioning
confidence: 99%
“…Formalin-fixed hemispheres were embedded in paraffin and cut into 4-μm-thick coronal sections using a rotation microtome (HM355S, Leica Biosystems GmbH, Nußloch, Germany) as described previously [ 75 , 76 , 77 , 204 , 205 , 206 , 207 , 208 , 209 , 210 ]. Sections (bregma +0.8 mm and −1.8 mm) were stained for microglia (IBA1, 1:1000, FUJIFILM Wako Chemicals Europe GmbH, 019–19741), astrocytes (GFAP, 1:500, Agilent, Santa Clara, CA, USA, Z033401-2) using a BOND-III ® automated immunostaining system (Leica Biosystems GmbH, Nußloch, Germany) with a hematoxylin counterstain (provided with the staining kit, Bond Polymer Refine Detection, DS9800).…”
Section: Methodsmentioning
confidence: 99%
“…They concluded that intraperitoneally administrated Aβ does not reach the brain from the periphery nor does it play any significant role in exacerbating brain amyloidosis. 19 Conversely, studies in guinea pigs and nonhuman primate models of cerebral amyloidosis have found that peripherally administered labeled-Aβ reaches the brain, contributes to parenchymal amyloidosis, and co-localizes with Aβ plaques 20,21 (Figure 1A). The discrepancies noted by the study from Brackhan et al may be explained by the source of the inoculum and/or the utilization of specific Tg mouse models that might generate distinct Aβ species that therefore result in differences in the rate of amyloid pathology progression.…”
Section: Role Of Peripheral Aβ Seeds In the Progression Of Brain Amyl...mentioning
confidence: 98%
“…18 In a more recent publication, Brackhan et al generated 13C-lysine-labeled human Aβ from Tg mouse brain extracts that were intraperitoneally injected into young Tg mice. 19 They detected the inoculated Aβ in the liver and lymphoid tissues but not in the brain of treated animals. They concluded that intraperitoneally administrated Aβ does not reach the brain from the periphery nor does it play any significant role in exacerbating brain amyloidosis.…”
Section: Introductionmentioning
confidence: 97%
“…And C57BL/6J mice genetically modified to synthesize human Aβ only in the liver have been reported to have increased plasma and brain Aβ ( Lam et al, 2021 ). On the other hand, intraperitoneal administration of 13 C-isotope-labeled brain extracts from mice expressing human Aβ to APP Tg mice resulted in long-term detection of injected Aβ in liver and lymphoid tissue but not in brain ( Brackhan et al, 2022 ). It remains unclear what effect peripheral Aβ has on Aβ deposition in the brain.…”
Section: Effect Of Alcohol On Blood Brain Barriermentioning
confidence: 99%